Geographies of Identity Narrative Forms, Feminist Futures - Darling, Jill (punctum books, 2021)
Geographies of Identity: Narrative Forms, Feminist Futures explores identity and American culture through hybrid, prose work by women, and expands the strategies of cultural poetics practices into the study of innovative narrative writing. Informed by Judith Butler, Homi Bhabha, Harryette Mullen, Julia Kristeva, and others, this project further considers feminist identity politics, race, and ethnicity as cultural content in and through poetic and non/narrative forms. The texts reflected on here explore literal and figurative landscapes, linguistic and cultural geographies, sexual borders, and spatial topographies. Ultimately, they offer non-prescriptive models that go beyond expectations for narrative forms, and create textual webs that reflect the diverse realities of multi-ethnic, multi-oriented, multi-linguistic cultural experiences. Readings of Gertrude Stein's A Geographical History of America, Renee Gladman's Juice, Pamela Lu's Pamela: A Novel, Claudia Rankine's Don't Let Me Be Lonely, Juliana Spahr's The Transformation, Theresa Hak Kyung Cha's Dictée, Gloria Anzaldúa's Borderlands/La Frontera, and Layli Long Soldier's WHEREAS show how alternatively narrative modes of writing can expand access to representation, means of identification, and subjective agency, and point to horizons of possibility for new futures. These texts critique essentializing practices in which subjects are defined by specific identity categories, and offer complicated, contextualized, and historical understandings of identity formation through the textual weaving of form and content.